The conserved histone deacetylase Rpd3 and the DNA binding regulator Ume6 repress BOI1's meiotic transcript isoform during vegetative growth in Saccharomyces cerevisiae. Issue 4 (21st March 2015) - Liu, Yuchen; Stuparevic, Igor; Xie, Bingning; Becker, Emmanuelle; Law, Michael J.; Primig, Michael
Summary BOI 1 and BOI2 are paralogs important for the actin cytoskeleton and polar growth. BOI1 encodes a meiotic transcript isoform with an extended 5′‐untranslated region predicted to impair protein translation. It is, however, unknown how the isoform is repressed during mitosis, and if Boi1 is present during sporulation. By interpreting microarray data from MATa cells, MATa/α cells, a starving MATα/α control, and a meiosis‐impaired rrp6 mutant, we classified BOI1's extended isoform as early meiosis‐specific. These results were confirmed by RNA‐Sequencing, and extended by a 5′‐RACE assay and Northern blotting, showing that meiotic cells induce the long isoform while the mitotic isoform remains detectable during meiosis. We provide evidence via motif predictions, an in vivo binding assay and genetic experiments that the Rpd3/Sin3/Ume6 histone deacetylase complex, which represses meiotic genes during mitosis, also prevents the induction of BOI1's 5′‐extended isoform in mitosis by direct binding of Ume6 to its URS1 target. Finally, we find that Boi1 protein levels decline when cells switch from fermentation to respiration and sporulation. The histone deacetylase Rpd3 is conserved, and eukaryotic genes frequently encode transcripts with variable 5′‐UTRs. Our findings are therefore relevant for regulatory mechanisms involved in the control of transcript isoforms in multi‐cellular organisms.